2020
DOI: 10.1038/s41598-020-76866-w
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for the detection of vertebral fractures on plain spinal radiography

Abstract: Vertebral fractures (VFs) cause serious problems, such as substantial functional loss and a high mortality rate, and a delayed diagnosis may further worsen the prognosis. Plain thoracolumbar radiography (PTLR) is an essential method for the evaluation of VFs. Therefore, minimizing the diagnostic errors of VFs on PTLR is crucial. Image identification based on a deep convolutional neural network (DCNN) has been recognized to be potentially effective as a diagnostic strategy; however, the accuracy for detecting V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 37 publications
4
77
0
3
Order By: Relevance
“…( 77 ) Twelve studies compared ML model performance versus human experts. ( 66,71,78–83,85,91,93,94 ) In four of these studies, ML outperformed human experts significantly. ( 80,83,85,91 ) Thirteen studies applied transfer learning based on pre‐defined CNN architectures, pre‐trained on the ImageNet data set ( 77,79–83,85,90,91,93,95 ) or on a radiography image database.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…( 77 ) Twelve studies compared ML model performance versus human experts. ( 66,71,78–83,85,91,93,94 ) In four of these studies, ML outperformed human experts significantly. ( 80,83,85,91 ) Thirteen studies applied transfer learning based on pre‐defined CNN architectures, pre‐trained on the ImageNet data set ( 77,79–83,85,90,91,93,95 ) or on a radiography image database.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 32 studies that investigated fracture detection (Table 3), (66–97 ) 11 were on vertebral fractures, ( 66–76 ) 17 hip fractures, ( 74–90 ) and 10 other fracture sites such as humerus or wrist. ( 75,76,90–97 ) Nineteen studies developed CNN models for image analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated that AI-based techniques can detect vertebral fractures on radiographs with very high accuracy. Both models achieved similar sensitivity and specificity to that achieved by expert surgeons and radiologists (26,(33)(34)(35)(36)(37) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review)…”
Section: Discussionmentioning
confidence: 92%